Straddling between Regulation and Innovation: A Case Study of an Islamic Bank in Indonesia. - Noval Adib; A.K. Siti Nabiha (Universitas Islam Negeri Jakarta, 2016)
Islamic bank, as an alternative financial institution, is now widely accepted and has been established in various countries. In Indonesia, Islamic bank was first established in 1992 along with the revival of Islam in the country. Previously, the establishment of Islamic bank in Indonesia was hindered not because of economical reason but because of a political stigma associated with Islam especially during the 1970s. The purpose of this article is to explore how the bank makes innovations to increase its performance that makes its legitimacy high on the eyes of its stakeholders. The article also discusses the various regulations and roles of central bank and the Indonesian government in ensuring control and good governance and subsequently into further developing the Islamic and shariah banking system in Indonesia.DOI: 10.15408/ajis.v16i1.2898